Analysis Of The Relationship Between Leg Muscle Strength And Leg Power In School Students' Athletic Performance - Muh Amiin; Hussein Ali Faqier; Allimar M Nuevo (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze the relationship between leg muscle strength and leg muscle power on students' athletic performance at school. Methodology: The method used is correlational research with a quantitative approach. The sample consisted of 19 students selected by purposive sampling. The instruments used include a leg dynamometer to measure leg muscle strength, and a vertical jump test to measure leg muscle power. Data analysis was performed using the Spearman's rho correlation test. Main Findings: The results showed a significant relationship between leg muscle strength and power and students' athletic performance (p = 0.046 < 0.05). This study confirms the importance of leg muscle strength and explosive power in supporting achievements in athletics, especially running and jumping. Novelty/Originality of this study: This study offers a novel insight by specifically examining the direct correlation between leg muscle strength and leg power as distinct yet interrelated components influencing athletic performance among school students a demographic often overlooked in biomechanical performance research. The findings provide new evidence on how targeted development of these physical attributes can enhance students' performance in school-level athletics.